(untitled) (Historia, 2021)
Brigadier-General Wilfrid Malleson (1866–1946) received his commission into the Royal Artillery in 1886 and transferred to the Indian Army in 1904. He was relatively inexperienced in combat having served on the staff of Field Marshal Kitchener as part of the British military mission in Afghanistan. Malleson was later transferred to East Africa where the 2nd South African Division fell under his overall command during the catastrophic attack on Salaita Hill. This was the first occasion, since the formation of the Union Defence Force (UDF) in 1912, where a British officer commanded South African troops in battle – with disastrous consequences. There were deep underlying reasons behind the fledgling UDF’s first defeat at the hands of the veteran Germans, commanded by the wily Colonel Paul von Lettow-Vorbeck (1870–1964). Malleson’s lack of combat experience was a factor in the defeat, but more importantly, the uninspired plan of attack doomed the UDF to failure.